Extraction and Synthesis of Typical Carotenoids: Lycopene, β-Carotene, and Astaxanthin - Yuxuan Jiang; Jingyi Ye; Yadong Hu; Jian Zhang; Wenhui Li; Xinghu Zhou; Mingzhou Yu; Yiyang Yu; Jingwei Yang; Wenge Yang; Jinchi Jiang; Jie Cui; et al. (Molecules, 2024)
Carotenoids are tetraterpene compounds acting as precursors to vitamin A, with functions that include protecting eyesight, enhancing immunity, promoting cell growth and differentiation, and providing antioxidative benefits. Lycopene, β-carotene, and astaxanthin are particularly critical for health and have diverse applications in food, health products, and medicine. However, natural carotenoids are encased within cell structures, necessitating mechanical methods to disrupt the cell wall for their extraction and purification—a process often influenced by environmental conditions. Thus, improving the efficiency of carotenoid extraction from natural resources is of great interest. This review delves into the research progress made on the extraction processes, structures, and biological functions of carotenoids, focusing on lycopene, β-carotene, and astaxanthin. Traditional extraction methods primarily involve organic solvent-assisted mechanical crushing. With deeper research and technological advancements, more environmentally friendly solvents, advanced machinery, and suitable methods are being employed to enhance the extraction and purification of carotenoids. These improvements have significantly increased extraction efficiency, reduced preparation time, and lowered production costs, laying the groundwork for new carotenoid product developments.